Genome-Wide Investigation of the NAC Transcription Factor Family in Miscanthus sinensis and Expression Analysis Under Various Abiotic Stresses - Nie, Gang; Yang, Zhongfu; He, Jie; Liu, Aiyu; Chen, Jiayi; Wang, Shuan; Wang, Xia; Feng, Guangyan; Li, Dandan; Peng, Yan; Huang, Linkai; Zhang, Xinquan (Frontiers in Plant Science, 2021)
The NAC transcription factor family is deemed to be a large plant-specific gene family that plays important roles in plant development and stress responses. M. sinensis is commonly planted in vast marginal land as forage, ornamental grass or bioenergy crop which demand a relatively high resistance to abiotic stresses. The recent release of a draft chromosome-scale assembly genome of M. sinensis provided a basic platform for the genome-wide investigation of NAC proteins. In this study, a total of 261 M. sinensis NAC genes were identified and a complete overview of the gene family was presented, including gene structure, conserved motif compositions, chromosomal distribution and gene duplications. Results showed that gene length, molecular weight (MW), and isoelectric points (pI) of NAC family were varied, while gene structure and motifs were relatively conserved. Chromosomal mapping analysis found that the M. sinensis NAC genes were unevenly distributed on 19 M. sinensis chromosomes, and the interchromosomal evolutionary analysis showed that 9 pairs of tandem duplicates genes and 121 segmental duplications were identified, suggesting that gene duplication, especially segmental duplication, is possibly associated with the amplification of M. sinensis NAC gene family. The expression patterns of 14 genes from M. sinensis SNAC group were analyzed under high salinity, PEG and heavy metals, and multiple NAC genes could be induced by the treatment. These results will provide a very useful reference for follow-up study of the functional characteristics of NAC genes in the mechanism of stress-responsive and potential roles in the development of M. sinensis.